Pembelajaran Bermakna dalam Implementasi Deep Learning di Madrasah Ibtidaiyah: Persepsi Orang Tua Siswa Kelas VI - Siti Rodiyah (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Abstract Meaningful learning is a primary objective in the implementation of the deep learning approach in Madrasah Ibtidaiyah (MI). Meaningful learning emphasizes not only mastery of subject matter but also conceptual understanding, learning independence, critical thinking skills, and the development of students’ attitudes and character. Parents play an important role in observing the impact of learning on children’s behavior and study habits at home. This study aims to describe parents’ perceptions of meaningful learning within the implementation of deep learning among sixth-grade Madrasah Ibtidaiyah students. This study employed a quantitative approach using a survey method. The participants consisted of 30 parents of sixth-grade Madrasah Ibtidaiyah students in Central Jakarta. Data were collected through a four-point Likert-scale questionnaire covering indicators of conceptual understanding, learning independence and activeness, critical thinking skills, attitudes and character, and the impact of learning at home. Data were analyzed using descriptive statistics, including mean scores and percentages. The results show that parents’ perceptions of meaningful learning in the implementation of deep learning fall into the very meaningful category, with an average percentage of 80.58%. These findings indicate that the implementation of deep learning contributes positively to the realization of meaningful learning among sixth-grade Madrasah Ibtidaiyah students. Abstrak Pembelajaran bermakna merupakan tujuan utama dalam implementasi pendekatan deep learning di Madrasah Ibtidaiyah (MI). Pembelajaran bermakna tidak hanya menekankan penguasaan materi, tetapi juga pemahaman konsep, kemandirian belajar, kemampuan berpikir kritis, serta pembentukan sikap dan karakter siswa. Peran orang tua menjadi penting sebagai pihak yang dapat mengamati dampak pembelajaran terhadap perilaku dan kebiasaan belajar anak di rumah. Penelitian ini bertujuan untuk mendeskripsikan persepsi orang tua terhadap pembelajaran bermakna dalam implementasi deep learning pada siswa kelas VI Madrasah Ibtidaiyah. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Subjek penelitian terdiri atas 30 orang tua siswa kelas VI Madrasah Ibtidaiyah di Jakarta Pusat. Data dikumpulkan menggunakan kuesioner skala Likert empat tingkat yang mencakup indikator pemahaman konsep, kemandirian dan keaktifan belajar, kemampuan berpikir kritis, sikap dan karakter, serta dampak pembelajaran di rumah. Data dianalisis menggunakan statistik deskriptif berupa perhitungan nilai rata-rata dan persentase. Hasil analisis menunjukkan bahwa persepsi orang tua terhadap pembelajaran bermakna dalam implementasi deep learning berada pada kategori sangat bermakna dengan persentase rata-rata sebesar 80,58%. Temuan ini menunjukkan bahwa implementasi deep learning berkontribusi positif dalam mewujudkan pembelajaran bermakna pada siswa kelas VI Madrasah Ibtidaiyah.